(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the characteristics of dyslipidemia and treatment outcomes in patients with type 2 diabetes mellitus at the Outpatient Department of Tan Phu General Hospital. Subjects and methods: A prospective descriptive study with before-after comparison was conducted on 107 patients with type 2 diabetes mellitus who required treatment for dyslipidemia from April to September, 2024. Lipid profiles were assessed at baseline and after 3 months of treatment. Treatment outcomes were evaluated based on LDL-C targets according to cardiovascular risk stratification. Data were analyzed using Stata 15.1. Results: The mean age was 61 ± 10 years and 57.01% were female. Most patients were classified as high or very high cardiovascular risk (99.09%). The prevalence of dyslipidemia was 89.72%, with hypertriglyceridemia (69.16%), elevated non-HDL-C (58.88%) and low HDL-C (42.06%) being the most common abnormalities. After 3 months of treatment, 16.82% of patients achieved LDL-C targets. Moderate-intensity Statin were the most commonly prescribed therapy (71.96%). Duration of diabetes and lipid-lowering therapy were significantly associated with LDL-C control (p < 0.05). Conclusion: Dyslipidemia is highly prevalent among patients with type 2 diabetes mellitus, while the proportion achieving LDL-C targets remains low. Optimizing Statin intensity and appropriate combination therapy according to cardiovascular risk may improve lipid control.